2013
DOI: 10.1186/cc13151
|View full text |Cite
|
Sign up to set email alerts
|

The effect of excess fluid balance on the mortality rate of surgical patients: a multicenter prospective study

Abstract: IntroductionIn some studies including small populations of patients undergoing specific surgery, an intraoperative liberal infusion of fluids was associated with increasing morbidity when compared to restrictive strategies. Therefore, to evaluate the role of excessive fluid infusion in a general population with high-risk surgery is very important. The aim of this study was to evaluate the impact of intraoperative fluid balance on the postoperative organ dysfunction, infection and mortality rate.MethodsWe condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 30 publications
1
79
0
4
Order By: Relevance
“…8,9,13,14 Excessive perioperative fluid loading leads to extravascular fluid accumulation and weight gain, which corresponds with increased mortality and morbidity during the early postoperative period. 6,8,15 Several meta-analyses have reported that goaloriented fluid therapy significantly reduces renal and pulmonary postoperative complications, and accelerates the first bowel movement, the resumption of normal diet, and shortens the length of stay in hospital. Restrictive fluid administration reduces postoperative pneumonia and pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9,13,14 Excessive perioperative fluid loading leads to extravascular fluid accumulation and weight gain, which corresponds with increased mortality and morbidity during the early postoperative period. 6,8,15 Several meta-analyses have reported that goaloriented fluid therapy significantly reduces renal and pulmonary postoperative complications, and accelerates the first bowel movement, the resumption of normal diet, and shortens the length of stay in hospital. Restrictive fluid administration reduces postoperative pneumonia and pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%
“…Restrictive fluid administration reduces postoperative pneumonia and pulmonary edema. 6,15,16 An inappropriate fluid administration disturbs the liberation of atrial natriuretic peptide, and injures the endothelial glycocalix, leading to the damage of the vascular barrier and increased fluid shifts into the extravascular space. 7,17 This pathology may result in abnormal extravascular water content, tissue edema, and raised IAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,17 Angka mortalitas pada usia gestasi kurang dari 37 minggu berdasar atas kenaikan berat badan pascaoperasi didapatkan 32 pasien dengan angka mortalitas 78% (Tabel 3). Pasien neonatus yang lahir disebut prematur jika usia gestasi kurang dari 37 minggu, bayi prematur memiliki angka mortalitas pascaoperasi yang lebih tinggi dibanding dengan bayi lahir cukup bulan.…”
Section: 515unclassified
“…Inadequate fluid management may cause reduced cardiac output and oxygen delivery to damaged tissue, which is associated with an increased rate of postoperative complications [1] . On the other hand, overhydration can have equally severe consequences, such as acidosis, coagulation deficits and periph-eral and pulmonary edema [2][3][4][5] . Children undergoing surgery are at a higher risk for developing hyponatremia, defined as a plasma sodium level < 136 mmol/L, which causes cells to draw in excess water and swell.…”
Section: Introductionmentioning
confidence: 99%